The Impact of Glucagon-Like Peptide-1 on Bone Metabolism and Its Possible Mechanisms - Zhao, Chenhe; Liang, Jing; Yang, Yinqiu; Yu, Mingxiang; Qu, Xinhua (Frontiers in Endocrinology, 2017)
The impact of antidiabetic drugs on bone metabolism is drawing increasing attention due to the discovery of a correlation between type 2 diabetes mellitus (T2DM) and osteoporosis. Glucagon-like peptide-1 (GLP-1) receptor agonists are a novel and promising class of drugs for T2DM, which may also have clinical applications in bone tissue disorders. This review examines the impact of GLP-1 on bone metabolism, including enhancement of bone mineral density and improvement of bone quality. However, the precise effect of GLP-1 on fracture risk has not been unambiguously defined. This review also summarizes our current understanding of the mechanisms by which GLP-1 affects bone metabolism. GLP-1 may act on bone by promoting bone formation, inhibiting bone resorption, and affecting the coordination of the two processes. We describe molecular pathways and proteins, such as Wnt and calcitonin, that are associated with GLP-1 and bone tissue. The specific processes and related molecular mechanisms of the effects of GLP-1 on bone metabolism need to be further explored and clarified.